Investigating the influence of present and projected climate on the livelihood of small-scale farmers in the uThungulu District Municipality, KwaZulu Natal, South Africa - Botai, Joel (University of Pretoria, 2019)
Dissertation (MSc)--University of Pretoria, 2019.